Disputas de gênero no ambiente virtual do jogo League of Legends - Luiz Paulo Rocha Vinhal (2019)
Technological sophistication enabled the expansion and creation of new relational spaces, no longer limited by geographic borders, as an example, we can mention online games. The online environment, as an important part of the current cultural context, reveals social practices performed by players who seem to reproduce broader relational aspects. In this sense, such issues can be explored by Social Psychology, also considering notions of Cyberculture theories. This sociability is not exempt from violent aspects, since players can reproduce stereotypes and prejudices naturalized in our society which, consequently, can make the experience of playing aversive and harmful for certain participating groups. It is in this context that the research is developed, identifying how gender stereotypes are present in the daily life of games. Thus, the study presented aims to understand the dynamics of gender from the participation of women in the game League of Legends (LoL). The research is of documental character, since it uses textual records from Facebook groups related to the game. The two publications that were selected emerged spontaneously, that is, without any influence from the researcher, and the comments made by the group members from these triggers were analyzed. In total, 886 comments were submitted to analysis, which comprised two corpora: the first composed of 647 comments and the second composed of 239 comments. These corpora were submitted to lexical analysis and similarity analysis procedure, with the aid of the IRAMUTEQ software. Each corpus resulted in a dendrogram that presented four classes each, later classified into three categories to guide the discussion of the data. The category names are: 1) Sex, Gender and Skill; 2) Violence; and 3) Resistance. The similarity analysis generated, for the first publication, a graph with two cores (“woman” and “play”), while for the second publication the generated graph presented three cores (“woman”, “play” and “rage”) . The textual elements show a culture permeated by violent practices and based on gender stereotypes, associating the ability within the game to the gender of the player, in which femine being associated with low or negative performance. Violence is seen as a common and acceptable practice in certain circumstances. Finally, the data reveal that the existence of this violent behavior finds resistance among the participants of the game, who use speeches of equality, irony or social actions to combat prejudiced postures and negative behaviors within the game.